Peran Moderasi Motivasi Hedonis pada Pengaruh Promosi Penjualan terhadap Niat Penggunaan Ulang Layanan Dompet Elektronik di Kalangan Milenial - Zahra, Nafisah; Sanaji, Sanaji (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the role of moderation of hedonic motivation in sales promotion on repurchase intention to use e-wallets by millennials. This research uses an online survey method. The sampling technique used is judgmental sampling. The respondents are users of e-wallet branded OVO payments. The sample used was 215 respondents. Data is processed using Moderating Regression Analysis (MRA). This study indicates that sales promotions and hedonic motivation have a significant effect on repurchase intentions, but there is no significant relationship between sales promotions with hedonic motivation to strengthen the effect of sales promotions on repurchase intentions.